ENGLISH SPEAKING TEACHING METHODS FOR ELEMENTARY SCHOOL STUDENT AT KAMPUNG INGGRIS PONTIANAK - Viqri Rahmad Satria (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
This research aims to know speaking teaching methods used at Kampung Inggris Pontianak for elementary school students and tutor obstacles during teaching activity. The method applied in this research was qualitative approach with descriptive analysis. The data were collected from interview and observation with the owner of Kampung Inggris Pontianak, West Kalimantan. It was found that English speaking skill to elementary school students was separated into four levels; basic, intermediate 1, intermediate 2, and advanced. There are five methods applied by Kampung Inggris Pontianak to improve students English speaking skill. Flashcards, watching movies, listening, games, and singing. There were two kinds of obstacles that tutors face during the class. First, most of the tutors’ backgrounds were non-educational. So, they found it hard, sometimes, to control their elementary students who are very energetic. They might have English language competence. However, it is not adequate as their only competence to teach students compared to tutors with English educational background. Therefore, Kampung Inggris Pontianak holds micro-teaching practices to see tutor candidate performances before coming into class. Second, new students made many false answers on the placement test just to make them get into a lower level class than they are supposed to be. The researcher hopes this research will give knowledge to the reader of how tutors in Kampung Inggris Pontianak teaches speaking skills to their students.